Cytotoxicity Analysis of the Effects of Heterobasidion Annosum Mycelia and Cisplatin on Colon Adenocarcinoma (CACO-2) Cell Line - Sevim, Çiğdem; Ünal, Sabri; Bakır, Temel Kan; Karadeniz, Mertcan; Tgzd, Ali Taghizadeh (Cumhuriyet University, 2024)
Colorectal cancer ranks as the third most prevalent form of cancer and stands as the second leading cause of mortality. Both environmental and genetic risk factors contribute to its manifestation. Presently, 5-fluoruracil/leucovorin (5-FU/LV) remains the recommended course for adjuvant therapy in addressing this condition. Conversely, mushrooms, celebrated for their biologically active constituents, including valuable enzymes, have emerged as a captivating subject in diverse medical disciplines, particularly within the realm of cancer therapy, due to their promising therapeutic properties. This specific investigation aimed to conduct in vitro cytotoxic experiments using extracts obtained from Heterobasidion annosum micelles cultivated in a liquid malt extract medium. The pulverized extracts were dissolved in Dulbecco's Modified Eagle Medium (DMEM) at varied concentrations ranging from 25ng/mL to 200ng/mL and subsequently administered to colon adenocarcinoma (Caco-2) cells. The cytotoxic effects of both the fungus and cisplatin, a well-known anticarcinogenic agent, were examined at intervals of 24, 48, and 72 hours. The findings indicated a significant inhibition of cancer cell development within this timeframe. Moreover, a noteworthy discovery emerged, revealing that cisplatin, known for its efficacy in various cancer studies, substantially diminished the viability of cancer cells after 72 hours in comparison to the control group.
Keywords: Temel Farmakoloji; Biyoteknoloji ve Uygulamalı Mikrobiyoloji; Mikrobiyoloji; Cisplatin; Colon adenocarcinoma; Heterobasidion annosum; Basic Pharmacology; Onkoloji; 3. Good health